flexZhouse - Mohd Zairul (A+BE: Architecture and the Built Environment)
Central to this PhD research was the problem of the lack of affordable housing for young starters in Malaysia. The solutions for affordable housing that are available in the market do not truly solve the problem from the customer’s point of view. Hence, it was important to analyse the contributing factors associated with the term ‘affordability’. The term touches upon interconnected elements that cover many issues ranging from demand (housing needs, demographics, household income, quality housing) to supply (the authorities’ requirements, design, cost, sustainability and procurement). In this thesis, we discuss some of the problems related to the supply and demand issues and examine a possible intervention to solve the problem.